2015
DOI: 10.1016/j.ajpath.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

TMIGD1 Is a Novel Adhesion Molecule That Protects Epithelial Cells from Oxidative Cell Injury

Abstract: Oxidative damage to renal tubular epithelial cells is a fundamental pathogenic mechanism implicated in both acute kidney injury and chronic kidney diseases. Because epithelial cell survival influences the outcome of acute kidney injury and chronic kidney diseases, identifying its molecular regulators could provide new insight into pathobiology and possible new therapeutic strategies for these diseases. We have identified transmembrane and immunoglobulin domain-containing 1 (TMIGD1) as a novel adhesion molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 43 publications
9
71
0
1
Order By: Relevance
“…3a). It should be noted that similar differences in predicted size versus actual size have been observed previously for both TMIGD1 and TMIGD2, due to posttranslational modifications such as N -glycosylation1923. We then performed sphere-formation assays using SJSA-1, KHOS/NP and MG63 cells following overexpression of TMIGD3 i1, TMIGD3 i3 or A3AR.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…3a). It should be noted that similar differences in predicted size versus actual size have been observed previously for both TMIGD1 and TMIGD2, due to posttranslational modifications such as N -glycosylation1923. We then performed sphere-formation assays using SJSA-1, KHOS/NP and MG63 cells following overexpression of TMIGD3 i1, TMIGD3 i3 or A3AR.…”
Section: Resultsmentioning
confidence: 52%
“…TMIGD1 is implicated in cell differentiation and adhesion1920, whereas TMIGD2 is implicated in cancer immunosuppression as a receptor of HHLA2, a B7 family member21. However, there is no previous report about TMIGD3.…”
Section: Resultsmentioning
confidence: 99%
“…Cell permeability and TEER assays were performed as described [9]. Briefly, PAE cells expressing IGPR-1 or control vector were seeded on tissue culture polycarbonate membrane filters coated with collagen I (pore size, 3.0 mm) in 24-well Transwell plates at a seeding density of 5,000 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…IGPR-1 expression is highly conserved in higher mammals, but no obvious homolog of IGPR-1 is found in mouse or rat [8]. However,, transmembrane and immunoglobulin domain-containing 1 (TMIGD1), which is the second member of the IGPR-1 family of proteins, is expressed both in humans and rodents [9]. Ectopic expression of IGPR-1 in porcine aortic endothelial (PAE) cells increased cell aggregation and deletion of the extracellular domain of IGPR-1 abrogated its adhesive function, thereby demonstrating that IGPR-1 acts as a putative CAM in endothelial cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Transmembrane and immunoglobulin domain containing (TMIGD) family proteins are newly identified class of immunoglobulin (Ig) domain containing cell adhesion molecules (Ig-CAMs), which include TMIGD1, immunoglobulin and proline rich receptor-1 (IGPR-1) [10][11][12] and TMIGD3 13 , which also acts as a tumor suppressor 14 . Although originally described as a protector of renal epithelial cells from oxidative cell injury 15 , TMIGD1 is downregulated in human renal cancer and its re-expression in renal tumor cells inhibits cell proliferation, migration and tumor growth in mouse tumor xenograft 15 . More importantly, a recent whole genome sequencing of pre-invasive colorectal tumor revealed that expression of TMIGD1 is progressively lost in colon cancer 16 .…”
Section: Introductionmentioning
confidence: 99%